2014
DOI: 10.4329/wjr.v6.i6.329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative review of vertebroplasty and kyphoplasty

Abstract: The aim of this review is to compare the effectiveness of percutaneous vertebroplasty and kyphoplasty to treat pain and improve functional outcome from vertebral fractures secondary to osteoporosis and tumor conditions. In 2009, two open randomized controlled trials published in the New England Journal of Medicine questioned the value of vertebroplasty in treating vertebral compression fractures. Nevertheless, the practice of physicians treating these conditions has barely changed. The objective of this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 79 publications
(82 reference statements)
1
22
0
4
Order By: Relevance
“…Low-energy trauma occurs more frequently in females, with an increased prevalence related with the ages, whereas high-energy traumas are more frequent in males and are not related with older age. 1 Pathological VF is secondary to osseous involvement by a localized debilitating condition, mainly tumours. Most are due to malignancies such as myeloma and primary bone tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-energy trauma occurs more frequently in females, with an increased prevalence related with the ages, whereas high-energy traumas are more frequent in males and are not related with older age. 1 Pathological VF is secondary to osseous involvement by a localized debilitating condition, mainly tumours. Most are due to malignancies such as myeloma and primary bone tumours.…”
Section: Introductionmentioning
confidence: 99%
“…The spine is the most affected target by metastases. 1 Anatomically and functionally, the thoracic and lumbar spine can be divided into three regions-thoracic spine (T1-T10), thoracolumbar junction (T10-L2) and the lumbar spine (L3-L5). 2 The narrow spinal canal in this region predisposes to spinal cord damage resulting in a high incidence of neurological deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Although, this helped lower the complication rates especially in cement leak to a range of 4.8-39% in some reports. 5 Studies have shown that patients underwent kyphoplasty had immediate pain relief, height restoration with a mean of 4.7 mm mid vertebral body, 7,8 and an average kyphosis correction of 62.4%+/-16.7% (average 6.6°). 7,9 New fractures of adjacent vertebrae occurred for both procedures at rates that are higher than the general osteoporotic population but, approximately equivalent to the general osteoporotic population that had a previous vertebral fracture.…”
Section: Kyphoplastymentioning
confidence: 99%
“…The reported rate of cement extravasation was 11-76% when computerized tomography (CT) scans where used. 5 If leakage happened into the neural canal it could cause neurologic deficits. Other complications reported includes pulmonary embolism, infection, and incomplete stabilization.…”
Section: Vertebroplastymentioning
confidence: 99%
“…A retropulsed bone fragment and the presence of intra vertebral cleft are characteristic of benign compression fractures. Chronic vertebral compression fractures are characterized by morphologic changes with recovery of normal signal of the bone marrow ( Figure 7) (37).…”
Section: Non-traumatic Vertebral Fracturesmentioning
confidence: 99%